Oblique impact behavior of unidirectional natural fiber reinforced composites - Salim, Yusuf; Yahya, M. Y.; Israr, H. A.; Azwan, S.; Roslan, M. N.; Abdullah, M. N. (Institute of Advanced Studies in Education (IASE), 2018)
This research focuses on the low velocity oblique impact on unidirectional (UD) kenaf reinforces composite plate. This study summarizes oblique impacts testing with angle 0°, 8° and 13° on three laminated layers of UD kenaf fiber with orientation structures of [0°, 30°, 0°] and [0°, 60°, 0°]. Nowadays, market ready composites mostly made-up using synthetic fibers, one of main problem when using synthetic fiber is hard to decompose and make its harms to environment. Natural fibers have high potential for replacing synthetic fibers as main composite materials. Kenaf fibers were chosen in this study due to relatively good mechanical properties with environmental friendly advantages. Kenaf yarn with the size of 855 Tex (1.0 mm diameter) is being used for UD kenaf fabric on the composite. Compression technique was used to prepare the composite with epoxy polymer as its resin. UD kenaf composite was tested using high speed puncher machine at speed 1m/s. Total energy absorption, load over displacement curves and fragmentation profile of the UD Kenaf composite are analyzed. By increasing oblique angle, the total energy absorption will decrease, load over displacement curves become fall off and the fragmentation profile of the composite become smaller had been revealed.